Evaluation of radon gas levels in the indoor environment of houses in Albu Mahmid village in Kufa city, Iraq - Abd Oun AL-jamal Lina; Hamid Abbas Saif; Mohammed Hadi Qunoot; Obayes Esraa S.; Hayder Rand A. (E3S Web of Conferences)
The primary natural source of radiation in humans is the atmosphere. Individuals predominantly reside indoors, rendering the home the primary source of exposure to natural airborne radiation, particularly radon gas. It is the second leading cause of lung cancer, behind smoking. This study is to assess the levels of radon 222 (222Rn) in residences inside Albu Mahmid village, Kufa, Iraq. Multiple radiation metrics, including AED (annual effective dose) and CPPP (lung cancer cases per year per million individuals), were also computed. A sophisticated radon detector was employed to assess radon levels in these residences. The concentrations of 222Rn ranged from 34.8 ± 5.9 Bq/m3, with average values of AED and CPPP for radon being 0.14 mSv/y and 1.14, respectively. The World Health Organisation, the Environmental Protection Agency, and the International Commission on Radiological Protection assert that radon concentration levels were within internationally recognised thresholds. And did not provide a health hazard.